Assessment of Mental Health of Healthcare Professionals Working in the Infectious Diseases Units: Comparative Study - Maysaa Niama Aboalshon1 , Hayder H. AL-Hadrawi2 , Ammar Abbas Shalan2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Health care professionals working in infectious diseases units or hospitals are at higher risk for being affected by certain contagious pathogens than other professional groups through direct contact, equipment, and contaminated supplies; therefore, they are working under ongoing stress that negatively impacting their psychological well-being. Aims: This study aims to assess the mental well-being of healthcare professionals working in infectious diseases units and compare these results to the score of other healthcare professionals working in other units. Methodology: A comparative study design using a convenience sample of (N=300) healthcare professionals (150 working in the infectious diseases units and 150 working in different units). The General Health Questionnaire-28 was used to assess the mental health of study subjects. Results: Recent findings indicate a statistically difference between study group and comparative group (p= <0.05), which means that healthcare providers working in the infectious disease units are at higher risk for psychological disturbance than the comparative group. Moreover, other work factors are found to have significant relationship with professionals’ mental health, such as infection prevention trainings, years of experience in infectious diseases units, availability of personal protection equipment and hand hygiene, and number of patients in the unit. Conclusion: Working in high risk work environment increases the concern about personal safety and impose ongoing stress, which negatively influence professional’s mental well-being. More training about infection prevention and provide personal protection materials help reducing the risk of disease transmission among patients and to health care providers.